Effect of intermittent lighting in open houses on the economic efficiency in the producing table egg (Damascus University Journal of agriculture sciences, 2024)
The research was conducted at a private poultry house in Homs between 10 August, 2020 and 10 January, 2022. A total of 412-one day- old chicks of an egg laying hybrid (Hy-Line), producing white shell eggs, raised from one day old until 74 weeks old: chicks were randomly distributed into four groups with three replicates of 35 birds in each. All groups were under the natural decreased day light during rearing phase until first week, at the nineteenth week different lighting regimes were applied (during production phase), The first group (control) was subjected to an increased lighting system, the second group was subjected to an intermittent lighting system so that the period of darkness between two periods of illumination was two hours, the third group was subjected to an intermittent lighting system so that the period of darkness between two periods of illumination was three hours,  the fourth group was subjected to an intermittent lighting system so that the period of darkness between two periods of illumination was four hours, the following productive parameters were studied for each replicate:1-cost of one hen from one day old until 74 weeks old.2-Products value for one hen from.3-The profit toined from one hen from.Results showed lighting system of the fourth group hat the higher profit value wluich has increased  significantly by 19.23% from one hen from one day old until 74 weeks old in comparison to the control group.
Keywords: Intermittent Lighting; Open Houses; Eegg Laying Hen; Economic Efficiency.